FEMALE CHARACTERS IN THREE FANTASY NOVELS BY LEIGH BARDUGO - Azalia, Humaira Diaz; Sachmadi, Ida Farida; Manggong, Lestari (Serat: Journal of Literary & Cultural Studies, 2025)
Three fantasy books Shadow and Bone (2012), Six of Crows (2015), and Ninth House (2019)by Leigh Bardugo, feature three female characters in an ambiguous position by giving them conflicting characteristics. This study aims to show that these young adult novels present the female characters in an ambiguous position and how they have the characteristics of Women’s Writing. This study is done by analysing the female characters through the narrative of the story and through the characters themselves. The analysis found that the novel's narratives for the three female characters use contradictory actions by using the characteristics of witches and heroes thus making way for the ambiguous stance and by incorporating modern struggles that women go through showing the characteristics of Women’s Writing. It can be concluded that by using contradictory actions through the characteristics of witches and heroes in the three female characters, an ambiguous position could be portrayed and how through them, the characteristics of Women’s Writing can be seen.